Swedish athletes` adjustment patterns in the junior-to-senior transition - Franck, A.; Stambulova, N.; Ivarsson, A. (International Journal of Sport and Exercise Psychology, 2018)
The specific objectives of this study were: (a) to identify adjustment patterns in the junior-to-senior transition (JST) based on athletes` dynamics of adjustment during a two-and-a-half-year period, and (b) to describe the athletes` demographic, personal and transitional characteristics at the beginning of the JST that were related to the different adjustment patterns. This quantitative longitudinal study consisted of five measurements conducted approximately every six months over a two-and-a-half-year period. One instrument was used to measure the transition variables and three instruments to measure personal characteristics. In the first measurement, 101 club-based Swedish athletes with the mean age of 16.51 (SD = 1.32) took part. The latent profile analysis on athletes` perceived degree of adjustment provided three profiles with different patterns in the JST. Profile 1 had a progressive adjustment pattern, whereas the second profile had a regressive adjustment pattern, and the third profile had a sustainable adjustment pattern. The descriptive statistics and Cohen`s d indicated that there were differences (with variation in magnitude) between the three profiles at the first measurement in terms of how athletes perceived different transitional characteristics. Keeping a primary focus on sport (but also having attention to other spheres of life), high athletic identity and motivation to reach senior level were characteristics relevant for both progressive and sustainable adjustment patterns.